2021
DOI: 10.3390/pharmaceutics13040567
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Azelaic Acid Nanocrystal-Loaded In Situ Hydrogel in the Treatment of Acne Vulgaris

Abstract: Acne vulgaris is a common, multifactorial, inflammatory skin disease affecting the pilosebaceous unit. Topical therapy is the first choice in the treatment of mild to moderate acne, and azelaic acid (AZA) is one of the most commonly used drugs. The aim of this study was to evaluate the safety and efficacy of a low-dose azelaic acid nanocrystal (AZA-NC) hydrogel in the treatment of mild to moderate facial acne. The study was designed as a double-blind, randomized controlled trial. Patients were randomized to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Applying a product to the skin is easier and more palatable if it has enough spreadability. Furthermore, more skin may be covered by formulations that are simpler to disperse, which could improve their therapeutic effect [55] . Spreadability study shows the force fluctuation as a function of time, revealing formulation strength (firmness), stickiness, work of spreading (work of shear), and force of extrusion (work of adhesion).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying a product to the skin is easier and more palatable if it has enough spreadability. Furthermore, more skin may be covered by formulations that are simpler to disperse, which could improve their therapeutic effect [55] . Spreadability study shows the force fluctuation as a function of time, revealing formulation strength (firmness), stickiness, work of spreading (work of shear), and force of extrusion (work of adhesion).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, more skin may be covered by formulations that are simpler to disperse, which could improve their therapeutic effect. [55] Spreadability study shows the force fluctuation as a function of time, revealing formulation strength (firmness), stickiness, work of spreading (work of shear), and force of extrusion (work of adhesion). The strongest positive force that may deform a formulation is its firmness, and this can be used to determine the formulation's strength.…”
Section: Evalution Of Emulgel Formulationmentioning
confidence: 99%
“…Among 2461 potential studies, 206 satisfied the inclusion criteria (eFigure in the Supplement). Among included trials, 163 (79%) were for acne and 43 (21%) were for rosacea. Rosacea RCTs were more likely to include at least 1 PROM (67% [n = 29 of 43]) compared with acne RCTs…”
Section: Resultsmentioning
confidence: 99%
“…If a product has sufficient spreadability, even applying it to the skin is simpler and more patient acceptable. Additionally, formulations that are easier to distribute might cover more skin upon application, which can enhance the therapeutic impact [40]. Spreadability results of our study are shown in Table 4.…”
Section: Spreadability Analysismentioning
confidence: 94%